PENGARUH EDUKASI TUMBUH KEMBANG ANAK DENGAN BOOKLET TERHADAP BERAT BADAN BALITA (24-59 BULAN) - Mahardany, Beauty Octavia; Supriadi, Rizky Febriyanti; Ahmady; Nanda Norisa; Aida Fitriani (LPPM STIKES Marendeng Majene, 2025)
Abstract. Stunting and undernutrition remain major public health challenges in Indonesia. Educational interventions are crucial, yet direct, periodic evaluations of print media's impact on children's weight gain are limited. This study aimed to analyze the effect of providing child growth and development education using a booklet medium on the weight gain of toddlers aged 24–59 months. A Quasi-Experimental One Group Pretest-Posttest Design with Repeated Measures was conducted, involving 30 toddlers selected via purposive sampling across Mamuju and West Aceh Regencies. The booklet-based educational intervention was administered and measured over four time points (pre-intervention, month 1, month 2, and month 3). Weight data were analyzed using Repeated Measures ANOVA and followed by a Post Hoc Bonferroni test (after Greenhouse-Geisser correction). Significance was set at ? = 0.05. The main analysis showed a highly significant effect of the education on toddler weight gain (F=40.875, p=0.000). The resulting effect size was large (?p2 = 0.585). The Post Hoc Bonferroni test confirmed that significant weight gain occurred between every time comparison (p ? 0.025). The repeated provision of child growth and development education using booklet media is proven to be highly effective as a strategy to increase and maintain toddler weight gain. This intervention is recommended for consistent integration and implementation within nutrition programs at the Posyandu or Primary Healthcare Center level. Abstrak. Gangguan pertumbuhan balita di Indonesia, khususnya stunting dan gizi kurang, masih menjadi tantangan utama. Intervensi edukasi merupakan strategi kunci, namun evaluasi langsung dan berkala terhadap dampak media edukasi cetak terhadap kenaikan berat badan balita masih terbatas. Penelitian ini bertujuan untuk menganalisis pengaruh pemberian edukasi tumbuh kembang anak menggunakan media booklet terhadap kenaikan berat badan balita usia 24–59 bulan. Penelitian ini menggunakan desain penelitian Quasi-Experimental One Group Pretest-Posttest Design with Repeated Measures, melibatkan 30 balita yang dipilih secara purposive sampling di Mamuju dan Aceh Barat. Intervensi berupa edukasi booklet diberikan dan diulang pada empat titik pengukuran (sebelum intervensi, bulan pertama, kedua, dan ketiga). Data berat badan dianalisis menggunakan Repeated Measures ANOVA, dilanjutkan Post Hoc Bonferroni (setelah koreksi Greenhouse-Geisser). Tingkat signifikansi ditetapkan ? = 0.05. Analisis utama menunjukkan adanya pengaruh yang sangat signifikan dari edukasi terhadap kenaikan berat badan balita (F=40.875, p=0.000). Effect size yang dihasilkan tergolong besar (?p2 = 0.585). Uji Post Hoc Bonferroni mengkonfirmasi bahwa kenaikan berat badan terjadi secara signifikan pada setiap perbandingan antar waktu (p ? 0.025). Pemberian edukasi tumbuh kembang anak menggunakan media booklet secara berulang terbukti sangat efektif sebagai strategi untuk meningkatkan dan mempertahankan kenaikan berat badan balita. Intervensi ini direkomendasikan untuk diintegrasikan dan diterapkan konsisten dalam program gizi di tingkat Posyandu atau Puskesmas.